Religion i systemteoretisk belysning - Götke, Povl (Religionsvidenskabeligt Tidsskrift, 1996)
The article is an introduction to the work of the German sociologist, Niklas Luhmann (born 1927), with special reference to some of the basic assumptions in his theory of religion. It is his point of view that religion first of all has a function on a social level as a certain kind of communication. Religion makes it possible for society to deal with the uncontrolled and the uncontrollable in a controlled manner. In other words, religion has something to do with contingency. Religion was formerly absolute in this respect, today there are a number of different and mutually competitive ways in order to deal with contingency. This is the result of differentiation, which is often referred to as the process of secularization. Secularization is a question of differentiation, Luhmann argues, not a question of rationalization.